2020
DOI: 10.1021/acs.jpcc.0c04126
|View full text |Cite
|
Sign up to set email alerts
|

The Balance between Charge Mobility and Efficiency in All-Solution-Processed Organic Light-Emitting Diodes of Zn(II) Coordination Compounds/PFO Composites

Abstract: Zn(II) coordination compounds with asymmetric salicylidene ligands in poly [9,9-dioctylfluorenyl-2,7-diyl] (PFO) composites were used for all-solution-processable white organic light-emitting diode (WOLED) purposes. These Zn(II) complexes were strategically synthesized to optimize their electronic structures, starting from the widespread known salophen core. Vertical excitation energies and natural transition orbital (NTO) densities of Zn(salicylidenes) were evaluated using density functional theory/time-depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 53 publications
3
7
0
Order By: Relevance
“…As we can see, by coordination with the metal, the salophen framework has undergone a considerable improvement in molecular planarity and symmetry, conferring molecular geometry that is close to the C 2v point group, as previously described elsewhere for Zn(II) coordination [ 51 , 53 ]. Nevertheless, in the case of the sal-3,4-ben ligand, regardless of the increase in planarity of the salophen moiety after coordination, its molecular structure still exhibits a non-symmetric system (C 1 point group), due to the presence of the benzoyl moiety.…”
Section: Resultssupporting
confidence: 65%
See 2 more Smart Citations
“…As we can see, by coordination with the metal, the salophen framework has undergone a considerable improvement in molecular planarity and symmetry, conferring molecular geometry that is close to the C 2v point group, as previously described elsewhere for Zn(II) coordination [ 51 , 53 ]. Nevertheless, in the case of the sal-3,4-ben ligand, regardless of the increase in planarity of the salophen moiety after coordination, its molecular structure still exhibits a non-symmetric system (C 1 point group), due to the presence of the benzoyl moiety.…”
Section: Resultssupporting
confidence: 65%
“…For comparison, we also recorded the PL spectrum of neat PFO (represented by the black curves in Figure 4 ). This spectrum is characteristic of PFO in a solid state, exhibiting a mixture of α-phase (amorphous) and β-phase, with the zero-phonon band at λ amorphous = 425 nm and λ β-phase = 437 nm, respectively [ 53 , 58 , 59 ]. The PFO spectra in the composites are different, indicating that the presence of the Pt(II) compounds impacts the PFO’s morphology.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 31–33 ] In addition, intramolecular charge transfer (ICT), fluorescence resonance energy transfer (FRET), and photo‐induced electron transfer (PET) are all in connection with hydrogen bonds. [ 34–40 ] Because Han and Zhao theoretically confirmed that hydrogen bonds are significantly enhanced after photoexcitation, the study of hydrogen bond dynamics has once again attracted wide attention. [ 41–46 ]…”
Section: Introductionmentioning
confidence: 99%
“…[31][32][33] In addition, intramolecular charge transfer (ICT), fluorescence resonance energy transfer (FRET), and photo-induced electron transfer (PET) are all in connection with hydrogen bonds. [34][35][36][37][38][39][40] Because Han and Zhao theoretically confirmed that hydrogen bonds are significantly enhanced after photoexcitation, the study of hydrogen bond dynamics has once again attracted wide attention. [41][42][43][44][45][46] Up to now, 3-hydroxychromone, 10-hydroxybenzoquinoline (HBQ), 3-hydroxyflavone (3-HF), fisetin, and other molecules that can react with ESIPT have been deeply explored.…”
Section: Introductionmentioning
confidence: 99%